Clinical Characteristics of Metastatic Colorectal Cancer Combined with Gastrointestinal Perforation and Prognostic Value of Circulating Tumor DNA - Hong Yang; Dongwen Rong; Wenhui Yang (Emergency Medicine International)
Objective. To explore the clinical characteristics of metastatic colorectal cancer combined with gastrointestinal perforation and the prognostic value of circulating tumor DNA (ctDNA). Methods. A total of 97 patients with metastatic colorectal cancer and gastrointestinal perforation were enrolled as the research objects between February 2016 and January 2019. Their clinicopathological characteristics were statistically analyzed. Patients were divided into the death group (n = 78) and the survival group (n = 19) according to their survival status at 3 years after surgery. The ctDNA level between the two groups was compared. Also, its evaluation value on patient prognosis was analyzed. The survival time in patients with different levels of ctDNA was compared. Results. The clinical staging was stage T4 in patients with metastatic colorectal cancer combined with gastrointestinal perforation, including 70 cases (72.16%) aged ≥60 years and 27 cases (27.84%) <60 years. There were 61 males (62.89%) and 36 females (37.11%). There were 27 cases (27.84%) with primary site at left colon, 59 cases (60.82%) at right colon and 11 cases (11.34%) at rectum. There were 56 cases (57.73%) with number of metastatic organs ≥2 and 41 cases (42.27%) <2. There were 58 cases (59.79%) treated with VEGF inhibitor before perforation, 40 cases (41.24%) with lung metastasis, 72 cases (74.23%) with liver metastasis, 30 cases (30.93%) with pelvic metastasis, 24 cases (24.74%) with distant lymph node metastasis, 56 cases (57.73%) with obstruction, and 35 cases (36.08%) with diverticulum. According to survival status at 3 years after after surgery, patients were divided into the death group (n = 78) and the survival group (n = 19). The level of plasma ctDNA in the death group was higher than that in the survival group (P<0.05). The area under curve (AUC) of ctDNA for predicting survival of patients was 0.806. According to ctDNA expression, patients were divided into the high expression group (n = 57) and the low expression group (n = 40). The survival rate in the high expression group was lower than that in the low expression group (7.02% (4/57) vs 36.38% (15/40)) (P<0.001). The median survival time for the two groups was 18.20 and 28.10 months, respectively. Conclusion. Clinical characteristics of metastatic colorectal cancer combined with gastrointestinal perforation include elderly age, obstruction, and diverticulum. The expression of ctDNA has evaluation value for prognosis of patients.